Implementasi REST API Aplikasi Pendaftaran Siswa Baru di SMA Hikmah Yapis Papua Berbasis Android - Alfath, Muhammad; Ardiani, Farida (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
Registration of new students is a process that is usually carried out every year in educational institutions such as schools. New student registration is useful in screening prospective students who are selected to become students. In this research, the registration process for new students at SMA Hikmah Yapis Papua was carried out using a website. The problem of this research is how to implement the Android-based REST API application to register new students at SMA Hikmah Yapis Papua. The research methods used are interviews, observation and bibliometric research. This Android-based new student registration application was built using the Kotlin programming language and uses the Laravel framework as the API and the MySQL database as the database server. The result of this research is an Android-based REST API application for registering new students at SMA Hikmah Yapis Papua which is able to facilitate student registration and obtain information about the school.